Decidability of Systems of Set Constraints with Negative Constraints - Aiken, Alexander; Kozen, Dexter; Wimmers, Ed (BRICS Report Series, 1994)
Set constraints are relations between sets of terms. They have been used extensively in various applications in program analysis and type inference. Recently, several algorithms for solving general systems of positive set constraints have appeared. In this paper we consider systems of mixed positive and negative constraints, which are considerably more expressive than positive constraints alone. We show that it is decidable whether a given such system has a solution. The proof involves a reduction to a number-theoretic decision problem that may be of independent interest.